2009
DOI: 10.1177/0741932508327467
|View full text |Cite
|
Sign up to set email alerts
|

Using the Concrete-Representational-Abstract Sequence to Teach Subtraction With Regrouping to Students at Risk for Failure

Abstract: This study investigated the effects of the concrete—representational—abstract (CRA) instructional sequence on the subtraction performance of students identified as at-risk for mathematics failure. Although the CRA sequence has been demonstrated as effective for teaching a variety of mathematical skills and processes its effects when used to teach subtraction with regrouping have not been studied. This study examined the effects of CRA instruction on elementary students’ fluency in computing subtraction problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 7 publications
4
70
1
5
Order By: Relevance
“…In order to have a baseline measure of children's mathematics skills on a traditional, language-heavy, symbolheavy task, participants completed the KeyMath3 (Connolly, 2007), a developmental assessment of mathematical concepts that has been used frequently in research, including studies with exceptional populations (Baylor, 1998;Eaves, 1992;Flores, 2009;Kratochwill & Demuth, 1976;Tinney, 1975). 4 2 The parent questionnaire was available in both English and Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…In order to have a baseline measure of children's mathematics skills on a traditional, language-heavy, symbolheavy task, participants completed the KeyMath3 (Connolly, 2007), a developmental assessment of mathematical concepts that has been used frequently in research, including studies with exceptional populations (Baylor, 1998;Eaves, 1992;Flores, 2009;Kratochwill & Demuth, 1976;Tinney, 1975). 4 2 The parent questionnaire was available in both English and Spanish.…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that CRA-SI is effective in building mathematical fluency with place value, addition and subtraction of numbers, multiplication, regrouping, fractions, integers and algebra (Bulter et al, 2003, Flores, 2010Peterson et al, 1988;Maccini & Hughes, 2000;Mercer & Miller, 1992;Morin & Miller, 1998;Strozier et al, 2012;Witzel et al, 2003). A summary of the research studies chronicled by date is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Results indicated significant improvement in students' computation of addition or subtraction facts and in students' growth rates which were compared to growth rates established by Fuchs and Fuchs (1993). Flores (2009Flores ( , 2010 extended the CRA-SI line of research to include subtraction with regrouping. This study investigated the effectiveness of the CRA sequence on the computation performance of students with specific learning disabilities and students identified as at risk for failure in mathematics.…”
Section: Cra-si For Multiplication Fluencymentioning
confidence: 99%
See 1 more Smart Citation
“…This theory became the framework of the opinion that students' original mathematics knowledge should be taught using concrete representations as manipulation objects. Manipulatives are used to promote conceptual understanding [21] and are frequently used to solve mathematics problems related to the concrete world. The results of research performed by [22] showed that students with high ability could generate various ideas in mathematics problem-solving.…”
Section: Data Interpretationmentioning
confidence: 99%